Supercontinuum Generated Micro-structured Fibre for Optical Communications and Medical Applications - Begum, Feroza; Emeroylariffion Aba, Pg; Petra, Iskandar; Felix Kaijage, Shubi; Zou, Nianyu (International Journal of Engineering and Technology, 2018)
This paper proposes a simple highly nonlinear photonic crystal fibre (HN-PCF) for generating supercontinuum (SC) spectrum in telecommunication window. Hexagonal structured HN-PCF with two different air hole diameters was modelled for numerical simulation and various properties of proposed photonic crystal fibres were calculated using finite difference method, and analysed. It has been demonstrated that nonlinear coefficients values of 113 [Wkm]−1 at 1.0 μm, 71 [Wkm]−1 at 1.30 μm and 51 [Wkm]−1 at 1.55 μm are obtainable; with flattened chromatic dispersion. The remarkably low confinement loss of less than 10-5 dB/km is obtainable in the wavelength range of between 1.0 μm and 1.7 μm. Moreover, it has been shown that it is possible to generate wide SC spectrum using 1.0 ps input pulses to achieve longitudinal resolution of 1.5 μm and 1.1 μm at 1.06 μm and 1.31 μm centre wavelengths, respectively. This proposed HN-PCF may be applicable for supercontinuum spectrum generation and all-optical signal processing in the infrared region.